SHARIAH SOLUTION FOR EMPTY NEST SYNDROME AMONG ELDERLY PERSONS IN MALAYSIA - Baharuddin, Ahmad Syukran; Ahmad, Muhammad Hazim; Ismail, Wan Abdul Fattah Wan; Mutalib, ukman Abdul; Mamat, Zulfaqar; Addawiyah, Siti Robiatun (International Journal of Psychosocial Rehabilitation, 2020)
The world population is ageing. According to data from World Population Prospects: the 2019 Revision, by 2050, one in six people in the world will be over age 65 (16%), up from one in 11 in 2019 (9%). Meanwhile, empty-nest syndrome is a psychiatric condition that affects elders, who encounter feelings of grief, disappointment, anxiety, failure, difficulty in changing their responsibilities, and change in parenting as children leave their parents’ home. In 2020, 10.3% estimated population aged 60+ years and above are vulnerable to ’empty-nest’ syndrome in Malaysia. This is due to several factors such as living alone or being left by their children. This syndrome causes them to feel sad and become stressful and even worse, suffers from mental or physical health problems. Previous research and statistics proved that 29.9% of older people may have empty nest syndrome as a result of living alone or with just their spouse without the presence of child in 2014. The numbers has increased years after. Therefore, this preliminary analysis will discuss how shariah address empty nest syndrome among senior citizens in Malaysia as majority of Malaysian are Muslims. This qualitative study uses inductive and deductive approaches to obtain general and specific conclusions of primary and secondary data sources. The findings from this analysis show that there are several solutions that have been clearly stated in the Qur’an and al-Sunnah on empty nest syndrome. Indeed, Islam emphasizes a comprehensive solution not only from one side but also from various parties such as family, community or neighborhood, as well as the ruler or government who will ensure that the current proposed solution is more convincing and effective. This study suggests for further research to be conducted to solve empty-nest issue among elderly citizen as Malaysia is moving towards ageing population in 2030.